FORMATION AND DEVELOPMENT OF CHILDREN’S SKILLS OF IMROVISATION AND COMPOSITION AT SOL-FA LESSONS - Zavadska, Galina; Rauduvaite, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
A lot of music researchers consider musical improvisation and composition to be a mutually supplementing processes (Alperson, 1984; Sloboda, 1988; Sarath, 1996). Improvisation actively stimulates the development of children’s creative abilities. It stirs the imagination, develops musical ear, emotional receptivity, and the skill of embodying images into new consonances, musical colors (Azzara, 2008; Solis & Nettl, 2009; Burton & Taggart, 2011). During the process of improvisation learners spontaneously express their musical ideas and interact with musical content, while during the process of composition it is possible to stop, to think everything over, to correct something and change it. Improvising and composing at sol-fa lessons are classified as kinds of creative music making. This paper is concerned with the analysis of the types of creative tasks at group classes on sol-fa, as well as with the comparison of different approaches to and methods of the formation and development of creative skills in improvisation and composition in the initial stage. Research aim: to determine and characterize the specific features of using improvisation and composition at sol-fa lessons in the initial stage. Research methods: the analysis of pedagogical experience, the comparison of contemporary methodologies for teaching improvisation and composition.